1977
DOI: 10.1038/bjc.1977.235
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome complement and SV40 transformation of cells from patients susceptible to malignant disease

Abstract: A comparative study has been made of fibroblasts obtained from patients with differing susceptibilities to malignant disease, both with respect to their chromosome complements and their transformation with SV40 virus. Fibroblasts from 2 Bloom's syndrome patients were found not to have raised SV40 transformation rates and no correlation was found between chromosome abnormality per se and transformation. Of 2 cell types with greatly increased rates, one was derived from a neurofibromatosis patient and the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…family compared with the controls. This is in accordance with reports by WEBB and HARDING (1977) and RICCARDI and MARGOS (1981).…”
Section: Discussion Von Recklinghausen's Disease Is Transmitted Bysupporting
confidence: 94%
See 1 more Smart Citation
“…family compared with the controls. This is in accordance with reports by WEBB and HARDING (1977) and RICCARDI and MARGOS (1981).…”
Section: Discussion Von Recklinghausen's Disease Is Transmitted Bysupporting
confidence: 94%
“…In neurofibromatosis, no consistent chromosomal abnormality has ever been reported. In a chromosome study of skin fibroblasts from a family with neurofibromatosis, WEBB and HARDING (1977) found no deviation from controls with respect to breaks and gaps. Neither have any convincing karyotypic abnormalities been revealed by cytogenetic analyses of skin and tumour fibroblasts with conventional staining or G-banding (RICCARDI and M A R C~S 1981).…”
mentioning
confidence: 92%
“…However, Young [8] found that only one of five obligate FA heterozygotes and two of five possible heterozygotes (unaffected sibs) showed some degree of abnormality However, his assay system differed in certain key details from that employed by Todaro. Similarly, Webb and Harding [6] found elevated transformation rates in only one of two FA heterozygotes. Using a system that measures T-antigen expression at three days, we found consistently high values in 12 FA cases (mean = 26.…”
Section: Discussionmentioning
confidence: 82%
“…For instance, infection of normal human skin fibroblasts with SV40 was shown to give rise to a limited number of transformed colonies. However, with cells from Fanconi’s anaemia (FA) patients there was a 10–20-fold increase in the number of transformants, whilst transformation of cells from ataxia telangiectasia (AT) and Bloom’s syndrome patients occurred at normal levels (Todaro et al , 1966; Kersey et al , 1972; Webb et al , 1977; Webb & Harding, 1977).…”
Section: An Historical Perspectivementioning
confidence: 99%